Workability and compressive strength properties of high strength geopolymer mortars - Khan, M.; Shaikh, Faiz; Hao, Y.; Hao, Hong (2017)
Geopolymer is an attractive sustainable binder as compared to Ordinary Portland Cement (OPC) in concrete. Recent investigations show that mechanical properties of heat cured geopolymers are similar or comparatively better to those of OPC. However, the requirement of heat curing for fly ash geopolymer is not feasible for large scale cast in-situ structural applications. Partial replacement of fly ash with slag has led to the setting of geopolymer mixes at ambient temperature, however the existing combinations in literature realize medium to low compressive strengths at ambient temperature with reduced workability. In this study, high strength ambient cured geopolymer is formed by using low calcium fly ash, Ultra-Fine Fly Ash (UFFA) and ground granulated blast furnace slag (slag). The effect of partial replacement of fly ash with slag (at a higher proportion) and UFFA on the workability of mortar mixtures and the compressive strength gain from 3 to 28 days is presented. Other parameters investigated are the effects of sand/binder ratios and the influence of both air and water curing on the compressive strength development of geopolymer samples. The results suggested that the early age properties of geopolymer can be controlled effectively with the optimum inclusion of additives in low calcium fly ash. Very high compressive strength for geopolymer mixtures up to 110 MPa is achieved at 28 days of ambient air curing. Workability of mixtures decreased with an increase in the additives and sand/binder ratios. Inclusion of superplasticizer (1% by wt. of the binder) slightly improved the workability of mixes having sand/binder of 2.75.